2018
DOI: 10.1002/jmri.26285
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI model with dynamic contrast‐enhanced and diffusion‐weighted imaging enables breast cancer diagnosis with high accuracy

Abstract: Background The MRI Breast Imaging‐Reporting and Data System (BI‐RADS) lexicon recommends that a breast MRI protocol contain T 2 ‐weighted and dynamic contrast‐enhanced (DCE) MRI sequences. The addition of diffusion‐weighted imaging (DWI) significantly improves diagnostic accuracy. This study aims to clarify which descriptors from DCE‐MRI, DWI, and T 2 ‐weighted imaging are most strongly associated with a breast cancer diagnosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 40 publications
2
59
0
Order By: Relevance
“…Compared with Ha et al [21] who concluded that any T2 hypointense enhancing focus representing an interval change should be biopsied rather than undergo short-term follow-up, we found no significant difference in T2 signal intensity between benign and malignant lesions. This is in agreement with Zhang et al who also showed that T2-weighted imaging does not significantly contribute to differentiating benign from malignant lesions [22]. In addition, we found that DWI signal analysis did not contribute to the accuracy of assessing these lesions, which can in part be explained by its limited spatial resolution which makes it challenging to accurately evaluate sub-centimeter masses.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with Ha et al [21] who concluded that any T2 hypointense enhancing focus representing an interval change should be biopsied rather than undergo short-term follow-up, we found no significant difference in T2 signal intensity between benign and malignant lesions. This is in agreement with Zhang et al who also showed that T2-weighted imaging does not significantly contribute to differentiating benign from malignant lesions [22]. In addition, we found that DWI signal analysis did not contribute to the accuracy of assessing these lesions, which can in part be explained by its limited spatial resolution which makes it challenging to accurately evaluate sub-centimeter masses.…”
Section: Discussionsupporting
confidence: 92%
“…X-ray mammography screening is characterized by a high level of sensitivity in detecting abnormal breast masses, but relatively low specificity in assessing malignancies 1 . This has triggered an increasing interest in additional methods for clarifying ambiguous findings, especially using magnetic resonance imaging (MRI) to avoid the large number of unnecessary biopsies [2][3][4][5][6][7] . A recent and successful trend has been the use of abbreviated, contrastagent free protocols based on diffusion-weighted imaging (DWI) and T2-weighted acquisitions, especially in the light of the required short examination times and the possible side effects of Gadolinium containing contrast agents 8 , which is especially relevant when aiming to apply these techniques during the clarification process of routine screening 3,[9][10][11] .…”
Section: Influence Of Residual Fat Signal On Diffusion Kurtosis Mri Omentioning
confidence: 99%
“…The apparent diffusion coefficient (ADC) from diffusion‐weighted imaging (DWI) has been reported to improve the differentiation between benign and malignant breast lesions, 9–11 the latter typically showing restricted water molecule diffusivity. However, previous studies have reported variable results in sensitivity and specificity between malignant and benign lesions 12–15 …”
mentioning
confidence: 99%